CX3CR1 upregulation modulates microglial activation and preserves synapses in the hippocampus and frontal cortex of middle-aged mice - Liu, Jinfeng; Sun, Zhongqing; Liu, Xin; Chiu, Kin; Ma, Lan; Wang, Jiantao (Frontiers in Aging, 2025)
IntroductionThe aging brain shows alterations in microglial function, morphology, and phenotype, reflecting a state of chronic activation. CX3CR1 plays a critical role in regulating microglial chemotaxis, phagocytosis, and activation. However, its exact role in the aging brain is not well understood.MethodsIn this study, we examined the expression of CX3CR1 in the brains of middle-aged mice (10 months old) and explored its functional implications by measuring cytokine and scavenger receptor expression, analyzing microglial and astrocyte morphology, conducting proteomic profiling, and assessing synapse density in CX3CR1-deficient mouse brain.ResultsOur results showed that CX3CR1 was upregulated in the hippocampus and frontal cortex of middle-aged mice, with decreased IL-1α and IL-1β levels in the frontal cortex and increased SRA and RAGE levels in the hippocampus. Proteomic analysis revealed an enrichment of differentially expressed proteins (DE-proteins) in the cerebrum of middle-aged mice in GO pathways such as “synapse”, “translation”, and “ribosome”. Following CX3CR1 knockout in the middle-aged mice, TNF-α and IL-1α levels increased, while CD68, SRA, and RAGE levels decreased in the hippocampus. Similarly, CD68, CD36, SRB1, and RAGE levels decreased in the frontal cortex. The absence of CX3CR1 significantly altered microglial morphology, resulting in enlarged cell bodies and shortened processes in the hippocampus and frontal cortex. CX3CR1 deficiency also changed astrocyte morphology, leading to enlarged cell bodies and elongated processes in the hippocampus. Further proteomic analysis indicated that CX3CR1 deficiency affected protein levels in GO pathways such as “glutamatergic synapse” and “RNA splicing.” Additionally, we observed a reduction in synaptophysin-positive synapse density in both the hippocampus and frontal cortex of CX3CR1-deficient mice.DiscussionOur findings demonstrated that CX3CR1 was upregulated to maintain synaptic homeostasis probably through regulating microglial activation and phagocytosis in the brains of middle-aged mice. CX3CR1 may represent a promising therapeutic target for alleviating the effects of aging and preventing neurodegeneration.